1998
DOI: 10.1111/1467-9590.00073
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Permanent‐wave Trains in Nonlinear Systems

Abstract: Multiple permanent-wave trains in nonlinear systems are constructed by the asymptotic tailmatching method. Under some general assumptions, simple criteria for the construction are presented. Applications to fourth-order systems and coupled nonlinear Schrödinger equations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…In addition, there are abundant asymmetric solitary waves exemplified by the solutions (2.9). Studies on such solitary waves can be found in [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are abundant asymmetric solitary waves exemplified by the solutions (2.9). Studies on such solitary waves can be found in [7].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that they often dominate the long time solution evolution [5,6]. These waves and their stability have been investigated by Mesentsev and Turitsyn [8], Kaup et Yang [7] among others. The work in [g-10] showed that there exists a family of symmetric, single-humped and stable solitary waves with an arbitrary polarization.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Below, we use a simplified version of [18]'s method to construct multi-vector-soliton bound states in the coupled NLS equations [i.e., (2.4) and (2.5)], and reproduce the spacing formula (2.10). There are two reasons for our doing this: (i) to highlight the key ideas in the tail-matching method for the construction of multi-pulse bound states; (ii) to motivate a similar tail-matching idea for the linear-stability analysis of multi-pulse bound states (see Sec.…”
Section: Two-vector-soliton Bound States: a Reviewmentioning
confidence: 99%
“…In certain physical situations, when there are two wavetrains moving with nearly the same group velocities, their interactions are then governed by the coupled NLS equations [34,39]. For example, the coupled NLS systems appear in the study of interactions of waves with different polarizations [8], the description of nonlinear modulations of two monochromatic waves [30], the interaction of Bloch-wave packets in a periodic system [35], the evolution of two orthogonal pulse envelopes in birefringent optical fiber [29], the evolution of two surface wave packets in deep water [34], to name a few.…”
Section: Introductionmentioning
confidence: 99%